Risk of serious infections in patients with rheumatoid arthritis treated in routine care with abatacept, rituximab and tocilizumab in Denmark and Sweden. Issue 3 (5th March 2019) - Grøn, Kathrine Lederballe; Arkema, Elizabeth V; Glintborg, Bente; Mehnert, Frank; Østergaard, Mikkel; Dreyer, Lene; Nørgaard, Mette; Krogh, Niels Steen; Askling, Johan; Hetland, Merete Lund
Abstract : Objective: To estimate (1) crude and age-and gender-adjusted incidence rates (IRs) of serious infections (SI) and (2) relative risks (RR) of SI in patients with rheumatoid arthritis (RA) initiating treatment with abatacept, rituximab or tocilizumab in routine care. Methods: This is an observational cohort study conducted in parallel in Denmark and Sweden including patients with RA in Denmark (DANBIO) and Sweden (Anti-Rheumatic Treatment in Sweden Register/Swedish Rheumatology Quality Register) who started abatacept/rituximab/tocilizumab in 2010–2015. Patients could contribute to more than one treatment course. Incident SI (hospitalisations listing infection) and potential confounders were identified through linkage to national registries. Age- and gender-adjusted IRs of SI per 100 person years and additionally adjusted RRs of SI during 0–12 and 0–24 months since start of treatment were assessed (Poisson regression). Country-specific RRs were pooled using inverse variance weighting. Results: We identified 8987 treatment courses (abatacept: 2725; rituximab: 3363; tocilizumab: 2899). At treatment start, rituximab-treated patients were older, had longer disease duration and more previous malignancies; tocilizumab-treated patients had higher C reactive protein. During 0–12 and 0–24 months of follow-up, 456 and 639 SI events were identified, respectively. The following were the age- and gender-adjusted 12-month IRs for abatacept/rituximab/tocilizumab: 7.1/8.1/6.1 for Denmark and 6.0/6.4/4.7 for Sweden. The 24-month IRs were 6.1/7.5/5.2 for Denmark and 5.6/5.8/4.3 for Sweden. Adjusted 12-month RRs for tocilizumab versus rituximab were 0.82 (0.50 to 1.36) for Denmark and 0.76 (0.57 to 1.02) for Sweden, pooled 0.78 (0.61 to 1.01); for abatacept versus rituximab 0.94 (0.55 to 1.60) for Denmark and 0.86 (0.66 to 1.13) for Sweden, pooled 0.88 (0.69 to 1.12); and for abatacept versus tocilizumab 1.15 (0.69 to 1.90) for Denmark and 1.14 (0.83 to 1.55) for Sweden, pooled 1.13 (0.91 to 1.42). The adjusted RRs for 0–24 months were similar. Conclusion: For patients starting abatacept, rituximab or tocilizumab, differences in baseline characteristics were seen. Numerical differences in IR of SI between drugs were observed. RRs seemed to vary with drug (tocilizumab < abatacept < rituximab) but should be interpreted with caution due to few events and risk of residual confounding.